2017
DOI: 10.1111/wrr.12606
|View full text |Cite
|
Sign up to set email alerts
|

Decreased superficial surgical site infections, shortened hospital stay, and improved quality of life due to incisional negative pressure wound therapy after reversal of double loop ileostomy

Abstract: This single-center prospective, controlled observational study investigates the impact of incisional negative pressure wound therapy on wound healing processes and its potency to prevent superficial surgical site infections (SSSI) after reversal of a double loop ileostomy. Furthermore, this study gains insight in socioeconomic aspects, like duration of hospital stay and, for the first time, patient's quality of life during the incisional negative pressure wound treatment. To address this question, an intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 26 publications
2
21
1
1
Order By: Relevance
“…The results of our pilot study are comparable to outcomes presented by Poehnert et al regarding utility of ciNPWT after the stoma reversal procedure [16]. Although the authors revealed that the postoperative wound infection rate was lower in the ciNPWT group, the difference was not statistically significant, which is consistent with our outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…The results of our pilot study are comparable to outcomes presented by Poehnert et al regarding utility of ciNPWT after the stoma reversal procedure [16]. Although the authors revealed that the postoperative wound infection rate was lower in the ciNPWT group, the difference was not statistically significant, which is consistent with our outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…However, the study did not compare the wound-healing period between the two groups. Two additional studies evaluated the application of NPWT to ileostomy closure sites and demonstrated the efficacy of NPWT in reducing the SSI rate [17, 18]. However, these previous studies focused on patients with primary linear closure of stoma wounds and did not evaluate the wound-healing period.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, use of NPD reduced hospital stay and wound-related readmissions. These findings reflect those undergoing elective cardiothoracic, 21 vascular, 22 gynecological, 23 plastic, 24 colorectal, 25 and general surgeries, 26 as well as in patients with high-risk abdominal wounds. [27][28][29] Importantly, we found that the overall incidence of SSI (17.2%) and wound breakdown (10.6%) after emergency laparotomy is high.…”
Section: Discussionmentioning
confidence: 59%